2019
DOI: 10.1097/bor.0000000000000576
|View full text |Cite
|
Sign up to set email alerts
|

Postactivated B cells in systemic lupus erythematosus: update on translational aspects and therapeutic considerations

Abstract: Purpose of review This review summarizes recent insights and current understanding of the role of postactivated B cells in SLE and related pathogenic and potential therapeutic implications. Recent finding B cells are considered key players in SLE and experience from various B-cell-targeted therapies underlines their clinical relevance. In the last years, new insights have been obtained on B-cell abnormalities within the complex pathophysiology of SLE. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…In autoimmune diseases and infections, excessive activation of B cells leads to an accumulation of exhausted/post-activated peripheral B cells, characterized by hyporesponsiveness to activating stimuli and upregulated expression of regulatory markers, like PD1 and PDL1 (25,39,40). CD21 and CD11c both have been described to play a role on chronic cognate activation of B cells, and they are linked in several ways: Transcripts of ITGAX, encoding CD11c, are upregulated in CD21 − B cells, which qualify as memory B cells due to their class switched BCRs (16), or as anergic B cells due to their lower activation threshold and calcium mobilization upon B cell stimulation and their autoreactive BCR repertoire (17).…”
Section: Discussionmentioning
confidence: 99%
“…In autoimmune diseases and infections, excessive activation of B cells leads to an accumulation of exhausted/post-activated peripheral B cells, characterized by hyporesponsiveness to activating stimuli and upregulated expression of regulatory markers, like PD1 and PDL1 (25,39,40). CD21 and CD11c both have been described to play a role on chronic cognate activation of B cells, and they are linked in several ways: Transcripts of ITGAX, encoding CD11c, are upregulated in CD21 − B cells, which qualify as memory B cells due to their class switched BCRs (16), or as anergic B cells due to their lower activation threshold and calcium mobilization upon B cell stimulation and their autoreactive BCR repertoire (17).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, BCR signaling has been extensively studied. There was a general consensus that pathologically increased BCR signaling contributed to B cell overactivity and autoimmunity, but recent studies showed that B cells in autoimmune diseases, such as systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), and primary Sjögren's syndrome (pSS) displayed diminished phosphorylation of Syk and Btk upon BCR activation and share a phenotype of hyporesponsiveness toward BCR and TLR9 stimulation [1208][1209][1210]. This condition was termed anergic post-activated (APA) B cells and provided evidence for the relevance to analyze intracellular signal transduction cascades in B cells under different conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted August 31, 2022. ; https://doi.org/10.1101/2022.08.30.22279344 doi: medRxiv preprint with the p-Syk ratio in that the shorter the interval the lower the induction of p-Syk at day 60 relative to baseline (Figure 5D). Elevated basal p-Syk and reduced induction following BCR stimulation are hallmarks of certain chronic conditions such as autoimmunity and persisting pathogens, such as HIV, and are generally associated with distinct B-cell populations, many of which express reduced levels of CD21 (Schrezenmeier et al, 2019). Activation of B cells in response to SARS-CoV-2 infection and vaccination is also accompanied by a reduction in the expression of CD21 on B cells (Kardava et al, 2022;Rodda et al, 2022;Woodruff et al, 2020).…”
Section: Prior Sars-cov-2 Infection Alters B-cell Responses and Pheno...mentioning
confidence: 99%